Is national socioeconomic status related to prevalence of irritable bowel syndrome?. Issue 8 (August 2014) - Zhu, Jin‐Zhou; Yan, Tian‐Lian; Yu, Chao‐Hui; Wan, Xing‐Yong; Wang, Yu‐Ming; Li, You‐Ming
Abstract Background and Aim There are a multitude of cross‐sectional surveys that provide the prevalence of irritable bowel syndrome (IBS) in the community. However, the data regarding the influence of socioeconomic status on prevalence of IBS were sparse. This study is to investigate the possible relation between human development and prevalence of IBS, at national level. Methods EMBASE Classic, EMBASE, and MEDLINE were searched (until October 2013) to identify population‐based studies that reported prevalence of IBS. Human Development Index (HDI) was chosen to assess socioeconomic status at national level. Results Firstly, no correlation was observed between prevalence of IBS and national HDI (P = 0.848). Specifically, there was no statistical significance in prevalence between developing and developed countries (P = 0.319). Moreover, prevalence of IBS failed to witness a downtrend in worldwide over the past two decades. Interestingly, the ratio of female/male prevalence was correlated with national HDI according to linear regression analysis (r = 0.395), and the ratio in the developing was significant lower than that in the developed (P = 0.0394). Lastly, except methods of data collection (P < 0.000), it shows no difference between developing and developed countries in diagnostic criteria, IBS subtypes, and age distribution (P = 0.119, 0.327, and 0.845 respectively). Conclusions This study is the first time to investigate the relation between IBS prevalence and national socioeconomic status, with consideration of years, gender, and other factors. It demonstrates that national development is not a direct indicator for prevalence of IBS.